4
$\begingroup$

I would like to prove the inequality

$$\frac{x}{\sqrt{3x+2y+z}}+\frac{y}{\sqrt{3y+2z+x}}+\frac{z}{\sqrt{3z+2x+y}}\leq\sqrt{\frac{x+y+z}{2}},$$

where $x,y,z>0$. What I did so far is the following:

The inequality is homogeneous, thus we can assume $x+y+z=1$. When we square both sides of the inequality and use Cauchy-Schwartz on the left-hand side, it suffices to show:

$$\frac{x}{3x+2y+z}+\frac{y}{3y+2z+x}+\frac{z}{3z+2x+y}\leq \frac{1}{2}.$$ But I couldn't make any real progress from there. For example, we can write the left-hand side, using $x+y+z=1$, as

$$\frac{x}{2+x-z}+\frac{y}{2+y-x}+\frac{z}{2+z-y}.$$

This seems somehow simpler, but how can I proceed?

$\endgroup$
4
$\begingroup$

Now, we can use C-S again.

We need to prove that $$\sum_{cyc}\left(\frac{x}{3x+2y+z}-\frac{1}{3}\right)\leq\frac{1}{2}-1$$ or $$\sum_{cyc}\frac{2y+z}{3x+2y+z}\geq\frac{3}{2}$$ and $$\sum_{cyc}\frac{2y+z}{3x+2y+z}=\sum_{cyc}\frac{(2y+z)^2}{(2y+z)(3x+2y+z)}\geq$$ $$\geq\frac{9(x+y+z)^2}{\sum\limits_{cyc}(2y+z)(3x+2y+z)}=\frac{9(x+y+z)^2}{\sum\limits_{cyc}(5x^2+13xy)}\geq$$ $$\geq\frac{9(x+y+z)^2}{\sum\limits_{cyc}(6x^2+12xy)}=\frac{3}{2}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.